Blocking Caspase-1/Gsdmd and Caspase-3/-8/Gsdme pyroptotic pathways rescues silicosis in mice - Lulu Kang; Jinghong Dai; Yufang Wang; Peiliang Shi; Yujie Zou; Jingwen Pei; Yaqiong Tian; Ji Zhang; Visarut Codey Buranasudja; Jingyu Chen; Hourong Cai; Xiang Gao; et al. (PLoS Genetics, 2022)
Millions of patients suffer from silicosis, but it remains an uncurable disease due to its unclear pathogenic mechanisms. Though the Nlrp3 inflammasome is involved in silicosis pathogenesis, inhibition of its classic downstream factors, Caspase-1 and Gsdmd, fails to block pyroptosis and cytokine release. To clarify the molecular mechanism of silicosis pathogenesis for new therapy, we examined samples from silicosis patients and genetic mouse models. We discovered an alternative pyroptotic pathway which requires cleavage of Gsdme by Caspases-3/8 in addition to Caspase-1/Gsdmd. Consistently, Gsdmd-/-Gsdme-/- mice showed markedly attenuated silicosis pathology, and Gsdmd-/-Gsdme-/- macrophages were resistant to silica-induced pyroptosis. Furthermore, we found that in addition to Caspase 1, Caspase-8 cleaved IL-1β in silicosis, explaining why Caspase-1-/- mice also suffered from silicosis. Finally, we found that inhibitors of Caspase-1, -3, -8 or an FDA approved drug, dimethyl fumarate, could dramatically alleviate silicosis pathology through blocking cleavage of Gsdmd and Gsdme. This study highlights that Caspase-1/Gsdmd and Caspase-3/8/Gsdme-dependent pyroptosis is essential for the development of silicosis, implicating new potential targets and drug for silicosis treatment. Author summary Inhalation of crystalline silica for prolonged periods leads to silicosis, which remains a prevalent occupational disease among mine workers. Silicosis is featured by lung inflammation, pulmonary fibrosis, nodular lesions and eventual development of lung cancer. Millions of patients suffer from silicosis, but it remains an uncurable disease due to its unclear pathogenic mechanisms. Here, we examined samples from silicosis patients and genetic mouse models. We found that Gsdmd and Gsdme both critical for silicosis. If we treated mice with silica, the mice without these two proteins showed markedly attenuated silicosis pathology. Furthermore, we confirm the upstream proteins which activated Gsdmd and Gsdme are Caspase-1, -3 and -8. Those caspases also important for the maturation of IL-1β and IL-18, which are inflammatory cytokines. Finally, we found that inhibitors of Caspase-1, -3, -8 or an FDA approved drug, dimethyl fumarate, could dramatically alleviate silicosis pathology through blocking cleavage of Gsdmd and Gsdme. Our study clarifies the molecular mechanism of silicosis related pyroptosis, and implicates new potential targets and drug for silicosis treatment.